2014
DOI: 10.1007/s00125-014-3382-x
|View full text |Cite
|
Sign up to set email alerts
|

Pre-pregnancy fried food consumption and the risk of gestational diabetes mellitus: a prospective cohort study

Abstract: Aims/hypothesis Fried foods are frequently consumed in Western countries. However, the health effects of frequent fried food consumption in humans are not well understood. We aimed to prospectively examine the association between pre-pregnancy fried food consumption and risk of incident gestational diabetes mellitus (GDM). Methods We included 21,079 singleton pregnancies from 15,027 women in the Nurses’ Health Study II cohort. Since 1991 and every 4 years thereafter, we collected diet information, including … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
40
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 53 publications
(43 citation statements)
references
References 35 publications
1
40
0
2
Order By: Relevance
“…Frying may also improve food palatability by making the food crunchy and aromatic, which may in turn lead to excess consumption [6]. Apart from the high-energy content, frequent consumption of fried food is considered an indicator of unhealthy lifestyle and dietary habit [7,8]. Fried food consumption has been shown to be associated with increased risks of type 2 diabetes [9], high blood pressure [10], and metabolic syndrome [11], as well as increased general and central obesity [6,10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Frying may also improve food palatability by making the food crunchy and aromatic, which may in turn lead to excess consumption [6]. Apart from the high-energy content, frequent consumption of fried food is considered an indicator of unhealthy lifestyle and dietary habit [7,8]. Fried food consumption has been shown to be associated with increased risks of type 2 diabetes [9], high blood pressure [10], and metabolic syndrome [11], as well as increased general and central obesity [6,10].…”
Section: Introductionmentioning
confidence: 99%
“…Modifiable risk factors such as diet before or during early pregnancy may serve as a target for preventing GDM. Specifically, a recent study reported that frequent fried food consumption before pregnancy was significantly associated with a greater risk of incident GDM [7]. However, few epidemiological studies have been focused on maternal outcomes associated with fried food consumption during pregnancy.…”
Section: Introductionmentioning
confidence: 99%
“…Over the years, a number of pre-pregnancy dietary factors have been found to be significantly associated with GDM risk (Table 1). Among these, potentially harmful factors include sugar-sweetened beverages [15], heme iron intake [16], fried foods [17], animal fat [18] and animal protein [19], a diet low in carbohydrate but high in animal fat and protein [20], as well as an overall western dietary pattern as characterised by a high intake of red meat and processed meat, refined grain products, sweets, French fries and pizza [21]. A recent study using the NHS-II data reported that greater potato consumption was related to an increased GDM risk [22].…”
mentioning
confidence: 99%
“…A higher consumption of animal fat, especially red meat, was significantly related with the occurrence of gestational diabetes, whereas a higher consumption of plant proteins, especially nuts, was associated with a considerably lower risk [22]. Frequent consumption of fried products also increased the risk of gestational diabetes, especially when consumed ≥ 7 times weekly [23]. The adherence, before pregnancy, to the principles of the Mediterranean diet, DASH diet, and the Healthy Eating Index (HEI) was related with a lower relative risk of diabetes by 24%, 34%, and 46%, respectively [24].…”
Section: Gestational Diabetesmentioning
confidence: 92%